Pengaruh Model Pembelajaran Role Playing Terhadap Motivasi Belajar Siswa Pada Pembelajaran IPS Kelas IV UPTDSD Negeri 122390 Pematang Siantar - Nora Anggriani Sianturi; Assister Fernando Siagaian; Radode Kristianto Simarmata (CV. KAMPUS AKADEMIK PUBLISING, 2023)
The aim of the research is to achieve learning and educational goals and foster student learning motivation. Type of quantitative research, with experimental methods. The population in this study were all fourth grade students at the UPTD SD Negeri 122390 Pematang Siantar school consisting of 27 students. The research instrument used was a questionnaire of 25 questions with variable x (role playing learning model) and variable y (student learning motivation). Based on the results of this research, it shows that the influence of the role playing learning model on learning motivation has a positive relationship. The results of the analysis of research data, this research data is proven by a significant value for variable Negeri 122390 Pematangsiantar.